Habitat structure and breeding parameters of the white stork Ciconia ciconia in the Kolno Upland (NE Poland) - Nowakowski, Jacek J. (Museum & Institute of Zoology, 2003)
An investigation of the habitat structure in nesting territories and the breeding success of the White Stork population in an agriculture landscape of the Kolno Upland adjoining the Biebrza river valley was conducted in 1994-1997. From 85.7% (1997) to 96.8% (1994) of nests were occupied by pairs of storks. The percentage of nests without nestlings was exceptionally low (0%-5.7%). Broods with three nestlings made up the highest proportion, c. 41.7-44.6 % of all the nests occupied by pairs. The average number of nestlings in nests with young was lowest in 1997 (2.53); in 1994-1996 it had been significantly higher (2.84-3.06). Pairs with nests sited up to 100 m from the nearest wet meadows in the river valley have a higher average breeding success in comparison with the pairs whose nests are sited farther away. The White Stork population tended to inhabit the area near the edge of the river valley. In the nesting territories (an area of 1 km radius around the nest site) cereal crops, meadows, green crops, pastures and wet meadows constituted the greatest proportion of the habitat structure. The proportions of these habitat types varied significantly between the nests. There was a significant positive correlation between the number of nestlings raised and the proportion of wet meadows, peat bogs and water bodies in the nesting territories.
Bibliogr. s. 45-46
S. [39]-46 : il. ; 27 cm
Streszcz. pol. Nazwy taksonów także w jęz. łac.
Keywords: Bocian biały -- biologia lęgowa -- Polska -- Biebrzy, Dolina [KABA]; Bocian biały -- biologia lęgowa -- Polska -- Kolneńska, Wysoczyzna [KABA]; parametry rozrodu; terytoria gniazdowe; struktura środowiskowa; bocianowate; ptaki; Ciconia ciconia; Ciconiidae; Aves; 1994-1997